2004
DOI: 10.1093/hmg/ddh131
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate ameliorates phenotypic expression in a transgenic mouse model of spinal and bulbar muscular atrophy

Abstract: Spinal and bulbar muscular atrophy (SBMA) is an inherited motor neuron disease caused by the expansion of a polyglutamine (polyQ) tract within the androgen receptor. Unifying mechanisms have been implicated in the pathogenesis of polyQ-dependent neurodegenerative diseases including SBMA, Huntington disease and spinocerebellar ataxias. It has been suggested that mutant protein containing polyQ inhibits histone acetyltransferase activity, resulting in transcriptional dysfunction and subsequent neuronal dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
174
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(181 citation statements)
references
References 50 publications
6
174
0
1
Order By: Relevance
“…Actually, the therapeutic effect of an HDAC inhibitor was observed only within a narrow range of lower doses, and the effect changed to be toxic at higher doses in polyQ transgenic mice. 35 These results suggest that the use of HDAC inhibitors in polyQ diseases requires careful consideration to avoid causing a lethal degree of Ku70 acetylation. The present study focused on the toxicity of expanded polyQ derived from the causative gene (mutated ataxin3) of MJD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Actually, the therapeutic effect of an HDAC inhibitor was observed only within a narrow range of lower doses, and the effect changed to be toxic at higher doses in polyQ transgenic mice. 35 These results suggest that the use of HDAC inhibitors in polyQ diseases requires careful consideration to avoid causing a lethal degree of Ku70 acetylation. The present study focused on the toxicity of expanded polyQ derived from the causative gene (mutated ataxin3) of MJD.…”
Section: Discussionmentioning
confidence: 98%
“…Based on this hypothesis, the maintenance of histone acetylation by HDAC inhibitors, such as trichostatin A (TSA), has been examined for the reduction of polyQ toxicity. 3,34,35 However, an HDAC inhibitor was recently shown to induce apoptosis in neuroblastoma cells by increasing Ku70 acetylation and promoting Bax-mediated cell death. 14 Therefore, it is plausible that HDAC inhibitors have a 'double-edge' activity in the context of After 48 h, cells were harvested and immunoprecipitation was performed using 6A7 anti-Bax monoclonal antibody polyQ toxicity; they attenuate polyQ toxicity by maintaining histone acetylation in the nucleus, but promote Bax-mediated cell death by acetylating Ku70 in the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vivo studies have shown that treatment with HDAC inhibitors of a wide range of structures provide neuroprotective effects in models of various motor neuron disorders. [44][45][46][47] However, the roles of glia under therapeutic mechanisms of HDAC inhibitors were not investigated. Here we showed that the neurotrophic effects of VPA, a HDAC inhibitor of short-chain fatty acid structure, were associated with Figure 5 VPA is neuroprotective against LPS-induced DA neurodegeneration in rat primary mesencephalic neuronglia cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, pharmacological inhibitors of HDACs have also shown promise in preclinical models of diseases of muscle, including amyotrophic lateral sclerosis (Yoo & Ko, 2011), spinal muscular atrophy (Minamiyama et al ., 2004) and muscular dystrophy (Consalvi et al ., 2013). For example, HDAC inhibitors reduce fibrosis and improve muscle function in a mouse model of muscular dystrophy (Consalvi et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%